The usage of watermarking to store patient information and diagnosis in medical images - Razlinda , Abd Razak (2011)
This thesis focuses on the implementation of medical image watermarking in DICOM. Digital watermarking is the process of embedding information into a digital signal in a way that is difficult to remove. Watermarking methods applied to medical images embedding, an area known as a region of non interest (RONI) needs to be defined on the image to retain the original information. The watermarked image produced should have visual quality similar to its original version. Watermarked image algorithm will be embedding using least significant bit (LSB). LSB is used because of its simple technique. Watermark image consist of RONI where the LSB will embed and store the patient’s information and diagnosis. The pixels that will use for embed patient information is 2x2 pixels each of 8 value bits. To embed patient’s information and diagnosis, the text will convert into binary using ASCII code.